The Policy Gap. Global Mental Health in a Semi-Peripheral Country (Portugal, 1998-2016) - Tiago Pires Marques (Faculdade de Medicina de Botucatu (Unesp), 2017)
This paper analyzes the impact of the hegemonic paradigm of global mental health (GMH) on Portugal. We specifically argue that GMH in Portugal has effected a change of priorities in health policies, favoring the prevention and treatment of common mental disorders to the detriment of the deinstitutionalizing process. Diffused through the media, this model has negative effects, such as the medicalization of social suffering, the reorganization of mental health policy areas according to utilitarian criteria, and the risk of greater invisibility of users with serious psychiatric diagnoses. However, the GMH approach, bringing to the frontline the impact of all social policies on mental health, represents a new opportunity to politically address social suffering. Characterized as a semi-peripheral country, Portugal may be representative of observable trends in similar countries.